2010
DOI: 10.1002/eco.167
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem level assessment of environmentally based flow restrictions for maintaining ecosystem integrity: a comparison of a modified peaking versus unaltered river

Abstract: Although dams have impounded the majority of the world's altered watercourses, there is a growing awareness of the importance of mitigating or reversing some of the negative effects on aquatic ecosystems and the related services they provide. We used an ecosystem approach, including detailed studies on hydrology, geomorphology, invertebrates, fish, and food web dynamics on a river altered by waterpower production and a natural flowing river to assess system responses to a change in the altered flow regime (spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 56 publications
0
82
1
Order By: Relevance
“…Several studies have reported similar impoundment effects on benthic algae d 13 C signatures (Chen & Jia, 2009;Chessmen et al, 2009;Smokorowski et al, 2011). Unlike other studies that have demonstrated 15 N enrichment of benthic algae downstream from dams (Chessmen et al, 2009;Growns et al, 2013), our investigation found little difference in phytomicrobenthos d 15 N and fairly consistent d 15 N values for Cladophora and C 3 herbaceous plants across the study area.…”
Section: Isotopic Signatures Of Basal Sources and Omnivorous Fishescontrasting
confidence: 74%
See 1 more Smart Citation
“…Several studies have reported similar impoundment effects on benthic algae d 13 C signatures (Chen & Jia, 2009;Chessmen et al, 2009;Smokorowski et al, 2011). Unlike other studies that have demonstrated 15 N enrichment of benthic algae downstream from dams (Chessmen et al, 2009;Growns et al, 2013), our investigation found little difference in phytomicrobenthos d 15 N and fairly consistent d 15 N values for Cladophora and C 3 herbaceous plants across the study area.…”
Section: Isotopic Signatures Of Basal Sources and Omnivorous Fishescontrasting
confidence: 74%
“…Availability of primary production sources for aquatic consumers is influenced by hydrology (Roach et al, 2014), nutrient enrichment from agricultural and urban sources (Pingram et al, 2012), and dams that regulate flows in downstream reaches (Shannon et al, 2001;Hoeinghaus et al, 2007;Marty et al, 2008;Vörösmarty et al, 2010). Several studies concluded that flows released from reservoirs shifted diets of fishes and invertebrates in downstream reaches (Chester & Norris, 2006;Smokorowski et al, 2011), whereas other studies concluded no major effects (Chessmen et al, 2009;Rolls et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…To develop the scientific information necessary to design management tools that address both ecosystem integrity and energy efficiency, the DFO, the Ontario Ministry of Natural Resources and Forestry, Brookfield Renewable, and the University of Waterloo collaborated on a long-term, adaptive management experiment to test whether regulating ramping rates through hydroelectric turbines provided ecological benefits, while at the same time minimizing electricity production losses (Smokorowski et al 2011). The main purpose of this experiment was to determine if removing all operational constraints on ramping rates from a hydroelectric facility was detrimental to the downstream riverine ecology.…”
Section: Case Studymentioning
confidence: 99%
“…During the period of highest energy demand, power is generated and water is rapidly released producing much higher and faster flows that fluctuate daily (Jones, 2013). These fluctuating discharges below impoundments may alter benthic invertebrate assemblages downstream, as a result of higher velocities, increased bed instability, and altered water temperature and quality, leading to higher invertebrate drift rates (Troelstrup and Hergenrader, 1990;Bruno et al, 2009;Smokorowski et al, 2011). Flows created by dam operations modulate natural seasonal extremes, and reduce flood frequency, duration and predictability (Poff et al, 1997;Bunn and Arthington, 2002), affecting aquatic biological conditions downstream of dams (Poff and Zimmerman, 2010).…”
Section: Introductionmentioning
confidence: 99%